2020
DOI: 10.3390/microorganisms8081181
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Parameters Affecting the Distribution and Diversity of the Water Column Microbial Community in the High-Altitude Andean Lake System of La Brava and La Punta

Abstract: Due to the low incidence of precipitation attributed to climate change, many high-altitude Andean lakes (HAALs) and lagoons distributed along the central Andes in South America may soon disappear. This includes La Brava–La Punta, a brackish lake system located south of the Salar de Atacama within a hyper-arid and halophytic biome in the Atacama Desert. Variations in the physicochemical parameters of the water column can induce changes in microbial community composition, which we aimed to determine. Sixteen sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 95 publications
0
27
0
1
Order By: Relevance
“…Smith and Mason, 1991; Jones and Renault, 1994) and distribution/composition (qualitatively or quantitatively) of microbial communities (e.g. Baud et al ., 1997; Chen et al ., 2011; Núñez Salazar et al ., 2020).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Smith and Mason, 1991; Jones and Renault, 1994) and distribution/composition (qualitatively or quantitatively) of microbial communities (e.g. Baud et al ., 1997; Chen et al ., 2011; Núñez Salazar et al ., 2020).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The microbial community reported in this study was rich in species but was dominated by only a few of them, as previously suggested in SdU (Rubin et al ., 2017; Pérez‐Fernández et al ., 2019) and in other salt flats from the lithium triangle (Aguilar et al ., 2016, 2018; Farias et al ., 2017; Núñez Salazar et al ., 2020). Interestingly, the best adapted species to this polyextreme environment, members of Salinibacter , Halonotius and Halorubrum genera, are characterized by their pigmentation (Oren, 2013; DasSarma et al ., 2019; Durán‐Viseras et al ., 2019), an effective protection against the intense UV radiation affecting SdU (Gomariz et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…4). Pseudospirillum, an aerobic bacterial genus, was positively associated with silica, pH, and DO, as their relative abundance increased with an increase in these parameters (Núñez Salazar et al, 2020). It is reported that Microbacterium was linked to the reduction of nitrate to nitrite (Gobbetti and Rizzello, 2014), and plays a role in polycyclic aromatic hydrocarbon removal in soil (Sheng et al, 2009).…”
Section: Discussionmentioning
confidence: 99%